Comparative Analysis of Approaches to Teaching Students with Hearing Impairments and Students without Disabilities at a Technical University - O. A. Oreshkina; P. V. Slitikov (Moscow Polytechnic University, 2020)
This paper provides a comparative analysis of approaches to teaching natural sciences disciplines on the example of chemistry to hearing impaired students and students without disabilities. Hearing impaired students make up the most difficult category of students at university of a general type with a verbal form of education due to their hearing impairment and concomitant disturbances in body functions that cause their disability. The key problem of their training at technical university is the limited content accessibility of the disciplines of the natural science cycle, including chemistry. They can master these disciplines only as subjects of adapted (inclusive) basic professional educational programs with creating special (distinctive) learning conditions for them. The authors developed and tested a methodological approach to solving the problem of content accessibility of educational resources in chemistry for hearing impaired students at technical university by creating special conditions for their mastering, taking into account their limitations. Particular educational conditions include support of hearing impaired students by additional adaptational course of chemistry with a focus on individualized teaching applying a number of cognitive technologies. In this regard, the offered approach is compensatory in nature. It allows teachers to identify the individual educational and rehabilitation needs of students with hearing impairment and meet those using organizational, technological and pedagogical solutions, thus leveling their educational opportunities with ones of students without disabilities. Due to the use of assistive tools and technologies compatible with the educational environment, it is possible to make it accessible to various categories of students.